Expression of blaCTX-M2 and invA genes of Salmonella Heidelberg isolated from poultry by Qpcr - Gabriella Bassi das Neves; Denise Nunes Araújo; Eduarda Pick; Dinael Simão Bitner; Maiara Cristiane Brisola; Regiane Boaretto Crecencio; Lenita Moura Stefani (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2020)
Salmonellosis is a disease caused by a bacterium Salmonella, a gram negative bacilli found in many environments, responsible for significant economic losses in poultry, and of great impact on public health. Among more than 2500 serovars, S. Heidelberg seems to be more invasive causing disease of greater severity than other serovars. The objective of this study was to investigate, through real-time PCR (qPCR), differences in the expression of a virulent gene (invA) and an antibiotic resistance gene (blaCTXM-2) of S. Heidelberg isolated from poultry meat (slaughterhouses) and drag swabs (field). Even though all isolates showed the presence of the invA gene, there were differences in the expression among the isolates, where isolates from the field showed greater expression of invA compared to samples isolated from meat products. On the other hand, isolates from the slaughterhouses showed greater expression of the blaCTX-M2 than those isolated from field samples.